2021
DOI: 10.1038/s41467-021-21360-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic functional analysis of Leishmania protein kinases identifies regulators of differentiation or survival

Abstract: Differentiation between distinct stages is fundamental for the life cycle of intracellular protozoan parasites and for transmission between hosts, requiring stringent spatial and temporal regulation. Here, we apply kinome-wide gene deletion and gene tagging in Leishmania mexicana promastigotes to define protein kinases with life cycle transition roles. Whilst 162 are dispensable, 44 protein kinase genes are refractory to deletion in promastigotes and are likely core genes required for parasite replication. Phe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
130
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(136 citation statements)
references
References 70 publications
6
130
0
Order By: Relevance
“…However, as for ATM, VE-821-treated cells were significantly more sensitive to H 2 O 2 , suggesting that ATR may act during the response to oxidative stress, similar to ATM, though work is needed to validate ATR as the target of VE-821 and to assess whether inhibiting ATR also sensitizes cells to other genotoxins. Unlike in T. brucei, and perhaps consistent with the VE-821 inhibition data, ATR has been reported to be dispensable for L. mexicana survival in vitro, though effects of ATR loss were not investigated further (Baker et al, 2021).…”
Section: The Atr Kinasementioning
confidence: 65%
See 4 more Smart Citations
“…However, as for ATM, VE-821-treated cells were significantly more sensitive to H 2 O 2 , suggesting that ATR may act during the response to oxidative stress, similar to ATM, though work is needed to validate ATR as the target of VE-821 and to assess whether inhibiting ATR also sensitizes cells to other genotoxins. Unlike in T. brucei, and perhaps consistent with the VE-821 inhibition data, ATR has been reported to be dispensable for L. mexicana survival in vitro, though effects of ATR loss were not investigated further (Baker et al, 2021).…”
Section: The Atr Kinasementioning
confidence: 65%
“…T. brucei, T. cruzi, and Leishmania encode for 190 (Jones et al, 2014), 190 (Parsons et al, 2005, and 206 (Baker et al, 2021) PKs, respectively, with several aPKs identified and members of all ePK groups represented, except for tyrosine-like and tyrosine kinases (Figure 2B). Over the last decade, with the implementation of genome-wide and kinome-focused screens in T. brucei, the roles of PKs have been investigated during drug resistance (Alsford et al, 2012), cell cycle control (Jones et al, 2014), and in vivo survival (Fernandez-Cortes et al, 2017).…”
Section: Ddr Effector Kinases: What Goes On Downstream?mentioning
confidence: 97%
See 3 more Smart Citations